The Agency of Nature in Abhijanashakuntlam - Ramteke, Vishant (Journal of Advanced Research in English & Education, 2022)
Nature, as an invisible and active character, plays a significant role in Kalidasa’s Abhijanashakuntalam, impacting the lives of the characters in subtle yet profound ways. This paper explores the theme of nature as the invisible, active character in the drama, examining the ways in which Kalidasa portrays nature as an important force that shapes the lives of the characters. Nature’s role in the text is significant because it is not merely a backdrop but an integral part of it. This paper examines the ways in which nature is portrayed as an invisible, active character in Shakuntala and how it influences the play’s plot, themes, characters. It examines various ways in which nature has been personified by the playwright to accentuate the dominant central ideas of that nature holds. In order to prove my thesis I have taken into consideration the English translation of Kalidasa: The Loom of Time, a selection his plays and poems, translated and edited by Chandra Rajan, penguin classics. How to cite this article:  Ramteke VA. The Agency of Nature in Abhijanashakuntlam. J Adv Res Eng & Edu 2022; 7(4): 18-21. DOI: https://doi.org/10.24321/2456.4370.202216